Differential mast cell numbers and characteristics in human tuberculosis pulmonary lesions - Karen Magdalena Garcia-Rodriguez (Nature Portfolio, 2021)
Abstract Tuberculosis (TB) is still a major worldwide health threat and primarily a lung disease. The innate immune response against Mycobacterium tuberculosis (Mtb) is orchestrated by dendritic cells, macrophages, neutrophils, natural killer cells and apparently mast cells (MCs). MCs are located at mucosal sites including the lungs and contribute in host-defence against pathogens, but little is known about their role during Mtb infection. This study investigates the location and characteristics of MCs in TB lesions to assess their contribution to TB pathology. To this purpose, number, location and phenotype of MCs was studied in 11 necropsies of pulmonary TB and 3 necropsies of non-TB infected lungs that were used as controls. MCs were localised at pneumonic areas, in the granuloma periphery and particularly abundant in fibrotic tissue. Furthermore, MCs displayed intracellular Mtb and IL-17A and TGF-β immunostaining. These findings were validated by analysing, post-mortem lung tissue microarrays from 44 individuals with pulmonary TB and 25 control subjects. In affected lungs, increased numbers of MCs expressing intracellularly both tryptase and chymase were found at fibrotic sites. Altogether, our data suggest that MCs are recruited at the inflammatory site and that actively produce immune mediators such as proteases and TGF-β that may be contributing to late fibrosis in TB lesions.